Tread rubber composition and pneumatic tire

The tire tread rubber composition, with a focus on styrene butadiene rubber and butadiene rubber content and specific crosslinking agents, addresses the challenge of maintaining abrasion resistance and physical property consistency during heat aging, resulting in improved wear resistance and grip performance.

JP7662068B2Active Publication Date: 2025-04-15SUMITOMO RUBBER INDUSTRIES LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024006889
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-20
Filing Date
2024-01-19
Publication Date
2025-04-15
Estimated Expiration
2039-07-26

AI Technical Summary

Technical Problem

Existing tire tread rubber compositions face challenges in maintaining abrasion resistance and physical property consistency due to heat aging, with a need for improved performance beyond just heat resistance.

Method used

A tread rubber composition with a minimum 10% mass content of styrene butadiene rubber and butadiene rubber, combined with specific crosslinking agents like sulfur and 1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane, and adjusted for hardness and swell changes within defined limits to enhance wear resistance.

Benefits of technology

The composition achieves significant improvements in wear resistance and grip performance while maintaining stability in hardness and swell changes after heat aging, leading to enhanced tire durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662068000001
    Figure 0007662068000001
  • Figure 0007662068000002
    Figure 0007662068000002
  • Figure 0007662068000003
    Figure 0007662068000003
Patent Text Reader

Abstract

To provide tread rubber compositions and pneumatic tires which are excellent in abrasion resistance.SOLUTION: The present invention provides a tread rubber composition containing, based on 100 mass% of a rubber component, 10 mass% or more of styrene-butadiene rubber and 10 mass% or more of butadiene rubber, and having an absolute value of change in hardness before and after heat aging, |ΔHs|, satisfying the following relationship (1) and an absolute value of change in Swell before and after heat aging, |ΔSwell|, satisfying the following relationship (2): |ΔHs|≤3.0 (1) and |ΔSwell|≤20% (2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tread rubber composition and a pneumatic tire. [Background technology]

[0002] The physical properties of tires generally change from when they are new due to aging, and one of the main causes of this is deterioration due to heat during use. Techniques have been proposed to reduce the difference in physical properties between when the tire is new and when it is deteriorated, such as increasing mono-crosslinking of sulfur and reducing -SS- bonds (poly-crosslinking), which are easily broken by heat.

[0003] Furthermore, Patent Document 1 discloses a rubber composition containing isoprene-based rubber, butadiene rubber, silica, aromatic oil, a specific compound, etc., and having improved heat resistance, etc. However, there is a large demand for improved performance, and further improvements in abrasion resistance, etc. are desired. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-219124 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to solve the above problems and to provide a rubber composition for a tread and a pneumatic tire having excellent abrasion resistance. [Means for solving the problem]

[0006] The present invention relates to a rubber composition for treads, which has a styrene-butadiene rubber content of 10% by mass or more and a butadiene rubber content of 10% by mass or more in 100% by mass of the rubber component, and in which an absolute value of change in hardness before and after heat aging, |ΔHs|, satisfies the following formula (1), and an absolute value of change in swell before and after heat aging, |ΔSwell|, satisfies the following formula (2). |ΔHs|≦3.0 (1) |ΔSwell|≦20% (2)

[0007] The rubber composition preferably contains sulfur and a crosslinking agent other than sulfur. The rubber composition preferably contains only a crosslinking agent other than sulfur.

[0008] The rubber composition preferably contains 25% by mass or more of isoprene-based rubber in 100% by mass of the rubber component.

[0009] The present invention also relates to a pneumatic tire having a tread made of the rubber composition. Effect of the Invention

[0010] According to the present invention, the rubber composition for treads has a styrene-butadiene rubber content of 10% by mass or more and a butadiene rubber content of 10% by mass or more in 100% by mass of the rubber component, and the absolute value of change in hardness before and after heat aging, |ΔHs|, satisfies the above formula (1), and the absolute value of change in swell before and after heat aging, |ΔSwell|, satisfies the above formula (2). Therefore, the rubber composition for treads exhibits necessary performance such as grip performance as a rubber for tire treads, and also significantly improves abrasion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention is a rubber composition for treads, in which the content of styrene-butadiene rubber in 100% by mass of the rubber component is 10% by mass or more, the content of butadiene rubber is 10% by mass or more, and the absolute value of change in hardness before and after heat aging, |ΔHs|, and the absolute value of change in swell before and after heat aging, |ΔSwell|, satisfy the above formulas (1) and (2). This not only ensures the necessary grip performance, but also provides excellent abrasion resistance.

[0012] The reason why such an effect is obtained is not clear, but is presumed to be as follows. The hardness and degree of crosslinking of rubber are considered to be physical properties that are greatly affected by heat aging (thermal degradation). First, it was thought that the change in hardness and degree of crosslinking could be suppressed by crosslinking the polymer with a material having stronger bonds than -SS-. Then, in a compound rubber containing a specified amount of styrene butadiene rubber (SBR) and butadiene rubber (BR), the hardness Hs of the rubber and Swell were used as an index of the degree of crosslinking, and the knowledge was found that the performance difference between a new tire and a deteriorated tire could be suppressed by adjusting the absolute value of hardness change |ΔHs| before and after heat aging to satisfy formula (1) and the absolute value of Swell change |ΔSwell| before and after heat aging to satisfy formula (2). Therefore, it is presumed that excellent wear resistance can be obtained over a long period of time when the specified amount of SBR and BR is contained and formulas (1) and (2) are satisfied.

[0013] Since crosslinking with sulfur alone has a limit to the suppression of heat aging, it was thought that heat aging could be suppressed by using a technique such as using sulfur in combination with other crosslinking agents as a crosslinking agent or using a crosslinking agent that does not contain sulfur. For example, when 1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane is used as a crosslinking agent, this compound forms a bond called -S-(CH2)6-S- between polymers, and since this SC bond has a higher activation energy than the -SS- bond of sulfur and is less likely to break, it is presumed that the effect of suppressing heat aging is remarkable. In addition, when dicumyl peroxide is used as a crosslinking agent that does not contain sulfur, it is presumed that a strong effect of suppressing heat aging can be obtained because a strong CC bond is directly formed between the polymers without the crosslinking agent (dicumyl peroxide) entering between the polymers. Therefore, for example, when such a crosslinking agent is used, it is presumed that a rubber composition that satisfies formulas (1) and (2) can be provided and excellent wear resistance can be obtained.

[0014] In this way, the present invention solves the problem (objective) of improving abrasion resistance by configuring a rubber composition for treads that satisfies formulas (1) and (2) in a formulation that contains a specified amount of styrene-butadiene rubber and butadiene rubber. In other words, the parameters of formulas (1) and (2) do not define the problem (objective); the problem of the present application is to improve abrasion resistance, and the composition satisfies the parameters as a means to achieve this.

[0015] Here, examples of the methods for satisfying the above formulae (1) and (2) and the later-described formulae (1-1) and (2-1) include (a) a method using a crosslinking agent capable of forming bonds including SC bonds between polymers (1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane, etc.), (b) a method using a crosslinking agent capable of directly forming CC bonds between polymers (organic peroxide, etc.), (c) a method using sulfur in addition to (a) and / or (b) as necessary, (d) a method of blending fine carbon black, (e) a method of adjusting the contents of these, (f) a method of adjusting the contents of SBR and BR, and (g) a method of using a zinc dithiophosphate compound, which may be used alone or in appropriate combination.

[0016] From the viewpoint of abrasion resistance, the rubber composition (rubber composition after vulcanization) has an absolute hardness change value |ΔHs| (|Hs of the rubber composition after heat aging-Hs of the rubber composition before heat aging|) before and after heat aging that satisfies the following formula (1). |ΔHs|≦3.0 (1) Preferably, |ΔHs|≦2.5, more preferably |ΔHs|≦2.0, even more preferably |ΔHs|≦1.5, particularly preferably |ΔHs|≦1.0, and most preferably |ΔHs|≦0.5. Within the above range, there is little change in hardness Hs before and after heat aging, and excellent wear resistance tends to be obtained over a long period of time.

[0017] From the viewpoints of abrasion resistance and practical applicability as a tread rubber, it is preferable that the hardness (Hs) of the rubber composition before and after heat aging satisfies the following formula (1-1). 40≦Hs≦80 (1-1) Preferably, 50≦Hs≦75, more preferably 55≦Hs≦70, and even more preferably 60≦Hs≦68. Within the above range, excellent practicality and abrasion resistance as a tread rubber tend to be obtained. The lower limit or upper limit of Hs may be 50.0, 55.0, 60.0, 64.0, 64.5, 65.0, 65.5, 66.0, 66.5, 67.0, 67.5, 68.0, 68.5, 69.0, 69.5, 70.0, 71.0, 72.0, 73.0, 74.0, 75.0, or 76.0.

[0018] From the viewpoint of abrasion resistance, the rubber composition (rubber composition after vulcanization) has an absolute value of swell change before and after heat aging, |ΔSwell| (|Swell of rubber composition after heat aging - Swell of rubber composition before heat aging|) that satisfies the following formula (2). |ΔSwell|≦20% (2) Preferably, |ΔSwell|≦15%, more preferably |ΔSwell|≦10%, and even more preferably |ΔSwell|≦5%. Within the above range, there is little change in the degree of crosslinking (Swell) before and after heat aging, and excellent wear resistance tends to be obtained over a long period of time. In addition, |ΔSwell| may be 19% or less, 18% or less, 17% or less, 16% or less, 14% or less, 13% or less, 11% or less, 8% or less, or 4% or less.

[0019] From the viewpoint of abrasion resistance, it is preferable that the rubber composition has a Swell satisfying the following formula (2-1) both before and after heat aging. 150%≦Swell≦450% (2-1) Preferably, 200%≦Swell≦400%, more preferably, 230%≦Swell≦350%, and even more preferably, 250%≦Swell≦300%. Within the above range, excellent wear resistance tends to be obtained. The lower limit or upper limit of Swell may be 245, 262, 264, 268, 271, 279, 280, 283, 286, 288, 292, 296, 302, 304, 310, 311, 312, 316, 319, 320, 322, 327, 331, 335, 336, 339, or 341.

[0020] The heat aging is performed under heat aging conditions (100°C, 96 hours) in accordance with JIS K6257:2010. The hardness (Hs) of the rubber can be measured with a type A durometer in accordance with JIS K6253 "Testing method for hardness of vulcanized and thermoplastic rubbers", and ΔHs is the change in Hs before and after heat aging. Swell means the volume change (%) of the test piece (rubber composition after vulcanization) before and after immersion in toluene, and ΔSwell is the change in Swell (%) before and after heat aging.

[0021] The rubber composition contains styrene-butadiene rubber (SBR) as a rubber component.

[0022] In the rubber composition, the content of SBR in 100% by mass of the rubber component is 10% by mass or more, preferably 15% by mass or more, and more preferably 18% by mass or more, from the viewpoint of practicality for treads such as abrasion resistance and grip performance. The upper limit is not particularly limited, but is preferably 60% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. The lower limit or upper limit of the SBR content may be 20% by mass or 25% by mass.

[0023] The styrene content of SBR is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. The styrene content is preferably 60% by mass or less, more preferably 40% by mass or less, and even more preferably 25% by mass or less. By keeping it within the above range, good abrasion resistance tends to be obtained. Furthermore, the lower limit or upper limit of the styrene content may be 23.5% by mass. The styrene content is 1 It is calculated by H-NMR measurement.

[0024] The SBR is not particularly limited as long as it is a rubber having styrene units and butadiene units, and examples thereof include emulsion-polymerized styrene-butadiene rubber (E-SBR) and solution-polymerized styrene-butadiene rubber (S-SBR). The total content of styrene units and butadiene units in 100% by mass of rubber in SBR is, for example, 95% by mass or more, and may be 98% by mass or more or 100% by mass. These may be used alone or in combination of two or more.

[0025] The SBR may be either unmodified SBR or modified SBR. The modified SBR may be any SBR having a functional group that interacts with a filler such as silica, and examples of the modified SBR include terminal-modified SBR (terminal-modified SBR having the above-mentioned functional group at the terminal) in which at least one terminal of the SBR has been modified with a compound (modifier) ​​having the above-mentioned functional group, main-chain-modified SBR having the above-mentioned functional group in the main chain, main-chain-terminal-modified SBR having the above-mentioned functional group in the main chain and at least one terminal (for example, main-chain-terminal-modified SBR having the above-mentioned functional group in the main chain and modified with the above-mentioned modifier at least one terminal), and terminal-modified SBR modified (coupled) with a polyfunctional compound having two or more epoxy groups in the molecule and having a hydroxyl group or epoxy group introduced therein.

[0026] Examples of the functional group include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, and an epoxy group. These functional groups may have a substituent. Among them, an amino group (preferably an amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms), and an amide group are preferable.

[0027] Modifiers used in modified SBR include, for example, polyglycidyl ethers of polyhydric alcohols such as ethylene glycol diglycidyl ether, glycerin triglycidyl ether, trimethylolethane triglycidyl ether, and trimethylolpropane triglycidyl ether; polyglycidyl ethers of aromatic compounds having two or more phenol groups, such as diglycidylated bisphenol A; polyepoxy compounds, such as 1,4-diglycidylbenzene, 1,3,5-triglycidylbenzene, and polyepoxidized liquid polybutadiene; Epoxy group-containing tertiary amines such as 4,4'-diglycidyl-diphenylmethylamine and 4,4'-diglycidyl-dibenzylmethylamine; diglycidyl amino compounds such as diglycidyl aniline, N,N'-diglycidyl-4-glycidyloxyaniline, diglycidyl orthotoluidine, tetraglycidyl meta-xylylenediamine, tetraglycidyl aminodiphenylmethane, tetraglycidyl-p-phenylenediamine, diglycidyl aminomethylcyclohexane, and tetraglycidyl-1,3-bisaminomethylcyclohexane;

[0028] Amino group-containing acid chlorides such as bis-(1-methylpropyl)carbamic acid chloride, 4-morpholinecarbonyl chloride, 1-pyrrolidinecarbonyl chloride, N,N-dimethylcarbamic acid chloride, and N,N-diethylcarbamic acid chloride; epoxy group-containing silane compounds such as 1,3-bis-(glycidyloxypropyl)-tetramethyldisiloxane and (3-glycidyloxypropyl)-pentamethyldisiloxane;

[0029] Sulfide group-containing silane compounds such as (trimethylsilyl)[3-(trimethoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(triethoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(tripropoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(tributoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(methyldimethoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(methyldiethoxysilyl)propyl]sulfide, (trimethylsilyl)[3-(methyldipropoxysilyl)propyl]sulfide, and (trimethylsilyl)[3-(methyldibutoxysilyl)propyl]sulfide;

[0030] N-substituted aziridine compounds such as ethyleneimine and propyleneimine; alkoxysilanes such as methyltriethoxysilane, N,N-bis(trimethylsilyl)-3-aminopropyltrimethoxysilane, N,N-bis(trimethylsilyl)-3-aminopropyltriethoxysilane, N,N-bis(trimethylsilyl)aminoethyltrimethoxysilane, and N,N-bis(trimethylsilyl)aminoethyltriethoxysilane; amino groups and / or substituted amino groups such as 4-N,N-dimethylaminobenzophenone, 4-N,N-di-t-butylaminobenzophenone, 4-N,N-diphenylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(diphenylamino)benzophenone, and N,N,N',N'-bis-(tetraethylamino)benzophenone. (Thio)benzophenone compounds having a group; benzaldehyde compounds having an amino group and / or a substituted amino group, such as 4-N,N-dimethylaminobenzaldehyde, 4-N,N-diphenylaminobenzaldehyde, and 4-N,N-divinylaminobenzaldehyde; N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, N-phenyl-2-pyrrolidone, Nt-butyl-2-pyrrolidone, and N-methyl-5-methyl N-substituted pyrrolidones such as 2-pyrrolidone, N-substituted piperidones such as N-methyl-2-piperidone, N-vinyl-2-piperidone, and N-phenyl-2-piperidone; N-substituted lactams such as N-methyl-ε-caprolactam, N-phenyl-ε-caprolactam, N-methyl-ω-laurylolactam, N-vinyl-ω-laurylolactam, N-methyl-β-propiolactam, and N-phenyl-β-propiolactam; and

[0031] Examples of such compounds include N,N-bis-(2,3-epoxypropoxy)-aniline, 4,4-methylene-bis-(N,N-glycidylaniline), tris-(2,3-epoxypropyl)-1,3,5-triazine-2,4,6-triones, N,N-diethylacetamide, N-methylmaleimide, N,N-diethylurea, 1,3-dimethylethyleneurea, 1,3-divinylethyleneurea, 1,3-diethyl-2-imidazolidinone, 1-methyl-3-ethyl-2-imidazolidinone, 4-N,N-dimethylaminoacetophene, 4-N,N-diethylaminoacetophenone, 1,3-bis(diphenylamino)-2-propanone, and 1,7-bis(methylethylamino)-4-heptanone. The modification with the above compound (modifying agent) can be carried out by a known method.

[0032] As the SBR, for example, SBR manufactured and sold by ZS Elastomers Co., Ltd., JSR Co., Ltd., Asahi Kasei Co., Ltd., Zeon Corporation, and the like can be used.

[0033] The rubber composition contains a butadiene rubber (BR) as a rubber component.

[0034] In the rubber composition, the content of BR in 100% by mass of the rubber component is 10% by mass or more, preferably 15% by mass or more, and more preferably 18% by mass or more, from the viewpoint of abrasion resistance. The upper limit is not particularly limited, but is preferably 60% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. The lower limit or upper limit of the BR content may be 20% by mass or 25% by mass.

[0035] The cis content of BR is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more, with no particular upper limit. When it is within the above range, the effect tends to be better. The cis content of BR can be measured by infrared absorption spectroscopy.

[0036] The BR is not particularly limited as long as it is a polymer containing butadiene units as the main units, and for example, BR with a high cis content, BR with a low cis content, BR containing syndiotactic polybutadiene crystals, etc. can be used. These may be used alone or in combination of two or more. The content of butadiene units in 100% by mass of rubber in BR is, for example, 95% by mass or more, and may be 98% by mass or more or 100% by mass. Rubber containing butadiene units and styrene units corresponds to SBR, but does not correspond to BR.

[0037] The BR may be either unmodified or modified, and the modified BR may be modified BR having the above-mentioned functional group introduced therein. Commercially available products include those available from Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc.

[0038] The rubber composition preferably contains an isoprene-based rubber as a rubber component.

[0039] In the rubber composition, the content of the isoprene-based rubber in 100% by mass of the rubber component is preferably 25% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more. The upper limit is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. Within the above range, good abrasion resistance tends to be obtained. Furthermore, the lower limit or upper limit of the content of the isoprene-based rubber may be 50% by mass or 60% by mass.

[0040] The isoprene-based rubber is not particularly limited as long as it is a polymer containing isoprene units as the main units, and examples thereof include isoprene rubber (IR), epoxidized isoprene rubber, hydrogenated isoprene rubber, grafted isoprene rubber, natural rubber (NR), deproteinized natural rubber (DPNR), highly purified natural rubber (UPNR), epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), grafted natural rubber, and the like. These may be used alone or in combination of two or more. The isoprene-based rubber has an isoprene unit content of 95% by mass or more, or may be 98% by mass or more, or may be 100% by mass, in 100% by mass of rubber.

[0041] The rubber component used in the rubber composition may contain other rubber components in addition to SBR, BR, and isoprene-based rubber. Examples of other rubber components include chloroprene rubber (CR) and acrylonitrile butadiene rubber (NBR). These may be used alone or in combination of two or more.

[0042] From the viewpoint of abrasion resistance, the rubber composition preferably contains fine particle carbon black.

[0043] The nitrogen adsorption specific surface area (N2SA) of the fine carbon black is preferably 120 m 2 / g or more, more preferably 150m 2 / g or more, more preferably 160m 2 By setting the N2SA at or above the lower limit, a sufficient reinforcing effect is exhibited, and good abrasion resistance tends to be obtained. The N2SA of the fine particle carbon black is preferably 300 m 2 / g or less, more preferably 250m 2 / g or less, more preferably 200m 2 / g or less. By setting it below the upper limit, the dispersibility of the carbon black tends to be ensured. In addition, the lower or upper limit of the N2SA of the fine carbon black is 181m 2 / g is also acceptable. The N2SA of fine particle carbon black can be measured in accordance with JIS K 6217-2:2001.

[0044] The content of the fine particle carbon black is preferably 5 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 35 parts by mass or more, and particularly preferably 40 parts by mass or more, based on 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, good abrasion resistance tends to be obtained. The content of the fine particle carbon black is preferably 100 parts by mass or less, more preferably 80 parts by mass or less, and even more preferably 60 parts by mass or less. By making it equal to or less than the upper limit, dispersibility of the carbon black tends to be ensured. In addition, the lower limit or upper limit of the content of the fine particle carbon black may be 45 parts by mass.

[0045] The fine particle carbon black can be produced by the method described in, for example, JP-A No. 2000-319539 and JP-T No. 8-507555.

[0046] As the fine particle carbon black, for example, products manufactured by Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shinnikka Carbon Co., Ltd., Columbia Carbon Company, etc. can be used.

[0047] The rubber composition preferably contains silica, which can provide both good grip performance and good fuel economy.

[0048] The content of silica per 100 parts by mass of the rubber component is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more. The upper limit is preferably 80 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 40 parts by mass or less. By keeping it within the above range, there is a tendency that both grip performance and fuel efficiency performance can be achieved. In addition, the lower limit or upper limit of the content of the silica may be 20 parts by mass or 40 parts by mass.

[0049] The nitrogen adsorption specific surface area (N2SA) of the silica is preferably 40 m 2 / g or more, more preferably 80m 2 / g or more, more preferably 100m2 The N2SA is preferably 300m 2 / g or less, more preferably 200m 2 / g or less, more preferably 180m 2 / g or less. By setting it within the above range, good wear resistance tends to be obtained. In addition, the lower limit or upper limit of the N2SA of silica is 175m 2 / g is also acceptable. The nitrogen adsorption specific surface area of ​​silica is a value measured by the BET method in accordance with ASTM D3037-81.

[0050] Examples of silica include dry silica (anhydrous silica) and wet silica (hydrated silica), and wet silica is preferred because it has a large number of silanol groups. For example, products available from Degussa, Rhodia, Tosoh Silica, Solvay Japan, Tokuyama, etc. can be used.

[0051] The rubber composition may contain fillers (reinforcing fillers) other than carbon black and silica. The other fillers are not particularly limited, and examples thereof include calcium carbonate, talc, alumina, clay, aluminum hydroxide, aluminum oxide, and mica.

[0052] The content of the filler is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 55 parts by mass or more, and particularly preferably 65 parts by mass or more, based on 100 parts by mass of the rubber component. By making it equal to or more than the lower limit, abrasion resistance tends to be improved. In addition, the content of the filler is preferably 150 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 80 parts by mass or less. By making it equal to or less than the upper limit, good processability tends to be obtained. In addition, the lower limit or upper limit of the content of the filler may be 85 parts by mass.

[0053] When the rubber composition contains silica, it is preferable that the rubber composition further contains a silane coupling agent, which tends to provide good strength and the like.

[0054] The content of the silane coupling agent is preferably 0.1 parts by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, based on 100 parts by mass of silica.The content is preferably 20 parts by mass or less, more preferably 16 parts by mass or less, and even more preferably 12 parts by mass or less.By keeping it within the above range, good grip performance tends to be obtained.

[0055] The silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-triethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamate, Examples of the silyl silane include sulfide-based silanes such as bamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 3-triethoxysilylpropyl methacrylate monosulfide; mercapto-based silanes such as 3-mercaptopropyl trimethoxysilane, 2-mercaptoethyl triethoxysilane, and NXT and NXT-Z manufactured by Momentive; vinyl-based silanes such as vinyl triethoxysilane and vinyl trimethoxysilane; amino-based silanes such as 3-aminopropyl triethoxysilane and 3-aminopropyl trimethoxysilane; glycidoxy-based silanes such as γ-glycidoxypropyl triethoxysilane and γ-glycidoxypropyl trimethoxysilane; nitro-based silanes such as 3-nitropropyl trimethoxysilane and 3-nitropropyl triethoxysilane; and chloro-based silanes such as 3-chloropropyl trimethoxysilane and 3-chloropropyl triethoxysilane. These may be used alone or in combination of two or more. Among these, sulfide-based and mercapto-based compounds are preferred because the above-mentioned effects can be obtained satisfactorily.

[0056] The rubber composition preferably contains an organic resin, which tends to provide good grip performance.

[0057] When the rubber composition contains an organic resin, the content (total content) of the organic resin is preferably 0.5 parts by mass or more, more preferably 1.5 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 5.0 parts by mass or less, more preferably 3.5 parts by mass or less. When the content is within the above range, good grip performance tends to be obtained.

[0058] As the organic resin, for example, a copolymer of an aromatic hydrocarbon and an aliphatic hydrocarbon can be suitably used.

[0059] The copolymer is a polymer (resin) containing aromatic hydrocarbons such as styrene and aliphatic hydrocarbons such as ethylene and propylene as constituent monomers, and commercially available products from Struktol, Performance Additives, etc. can be used. These may be used alone or in combination of two or more. Among them, a resin containing ethylene, propylene, and styrene as constituent monomers (ethylene propylene styrene copolymer) is preferred.

[0060] The softening point of the copolymer is preferably 20° C. or higher, more preferably 40° C. or higher, and even more preferably 60° C. or higher, and is preferably 140° C. or lower, and more preferably 100° C. or lower.

[0061] When the copolymer is an ethylene propylene styrene copolymer, the ethylene propylene content (EP content) in 100 mass% of the ethylene propylene styrene copolymer is preferably 70 mass% or more, more preferably 80 mass% or more, and preferably 98 mass% or less, more preferably 95 mass% or less.

[0062] From the viewpoint of achieving both abrasion resistance and processability, it is preferable to compound a softener in the rubber composition. A softener is a component that has a softening effect in a liquid state at room temperature (25°C). The softener is not particularly limited, but examples thereof include oil and liquid polymers (liquid diene-based polymers). These may be used alone or in combination of two or more.

[0063] The content (total content) of the softener is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 7 parts by mass or less. By keeping the content within the above range, good abrasion resistance and the like tend to be obtained. In this specification, the content of the softener includes the amount of oil contained in the oil-extended rubber.

[0064] The oil is not particularly limited, and may be any conventionally known oil, such as paraffin-based process oil, aromatic process oil, naphthenic process oil, low PCA (polycyclic aromatic) process oil such as TDAE or MES, vegetable oil, or mixtures thereof. Among these, aromatic process oil is preferred from the viewpoint of rubber physical properties.

[0065] For example, commercially available products that can be used include those from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., Japan Energy Co., Ltd., Orisoi Co., Ltd., H&R Co., Ltd., Toyokuni Oil Mills Co., Ltd., Showa Shell Sekiyu K.K., Fuji Kosan Co., Ltd., etc. These may be used alone or in combination of two or more kinds.

[0066] From the viewpoint of processability, the oil content is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, per 100 parts by mass of the rubber component. The content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 7 parts by mass or less. By keeping the content within the above range, good abrasion resistance and processability tend to be compatible. In this specification, the oil content includes the amount of oil contained in the oil-extended rubber.

[0067] The liquid polymer is a polymer that is in a liquid state at room temperature (25° C.), and examples thereof include liquid diene-based polymers. The liquid diene polymer has a weight average molecular weight (Mw) of 1.0×10 based on polystyrene standards, as measured by gel permeation chromatography (GPC). 3 ~2.0×10 5 Preferably, it is 3.0×103 ~1.5×10 4 It is more preferable that: In this specification, the Mw of the liquid diene polymer is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).

[0068] Examples of liquid diene polymers include liquid styrene-butadiene copolymer (liquid SBR), liquid butadiene polymer (liquid BR), liquid isoprene polymer (liquid IR), and liquid styrene-isoprene copolymer (liquid SIR).

[0069] The content of the liquid polymer (liquid diene polymer) is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, even more preferably 30 parts by mass or less, and particularly preferably 27 parts by mass or less.

[0070] The rubber composition (rubber composition after vulcanization) preferably contains a crosslinking agent. Examples of the crosslinking agent include sulfur (sulfur vulcanizing agent) and crosslinking agents other than sulfur (crosslinking agents capable of forming bonds including SC bonds between polymers, crosslinking agents capable of directly forming CC bonds between polymers, zinc dithiophosphate, etc.). Among these, the crosslinking agent is preferably a combination of sulfur and a crosslinking agent other than sulfur, or a crosslinking agent other than sulfur alone, and more preferably a combination of sulfur and a crosslinking agent capable of forming bonds including SC bonds between polymers, or a crosslinking agent capable of directly forming CC bonds between polymers alone, or a combination of sulfur and zinc dithiophosphate.

[0071] Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are commonly used in the rubber industry. Commercially available products include those from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanzuri Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. These may be used alone or in combination of two or more kinds.

[0072] The content of sulfur (sulfur vulcanizing agent) per 100 parts by mass of the rubber component is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more. The upper limit is preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 1.0 parts by mass or less. By setting the content within the above range, good abrasion resistance tends to be obtained. The lower limit or upper limit of the sulfur content may be 0.5 parts by mass.

[0073] As a crosslinking agent capable of forming bonds including SC bonds between the polymers, a compound represented by the following formula (I) can be suitably used, which allows the rubber composition to have CC bonds with high bond energy and high thermal stability. [ka] (In the formula, E is an alkylene group having 2 to 10 carbon atoms, R 101 and R 102 are the same or different and represent a monovalent organic group containing a nitrogen atom.

[0074] The alkylene group of E is not particularly limited, and examples thereof include linear, branched, and cyclic alkylene groups, with linear alkylene groups being preferred.

[0075] The number of carbon atoms in the alkylene group of E is 2 to 10, and preferably 4 to 8. If the alkylene group has only one carbon atom, the thermal stability is poor and the effect of having the alkylene group tends not to be sufficiently obtained, whereas if the alkylene group has 11 or more carbon atoms, it tends to be difficult to form a crosslinked chain represented by -SSESS-.

[0076] Examples of alkylene groups that satisfy the above conditions include ethylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, decamethylene, etc. Among these, the hexamethylene group is preferred because crosslinks represented by -SSESS- are smoothly formed between polymers and it is thermally stable.

[0077] R101 and R 102 R is not particularly limited as long as it is a monovalent organic group containing a nitrogen atom, but it is preferably one containing at least one aromatic ring, and more preferably one containing a linking group represented by NC(=S)- in which a carbon atom is bonded to a dithio group. 101 and R 102 may be the same or different, but are preferably the same for reasons such as ease of production.

[0078] Examples of the compound represented by formula (I) include 1,2-bis(N,N'-dibenzylthiocarbamoyldithio)ethane, 1,3-bis(N,N'-dibenzylthiocarbamoyldithio)propane, 1,4-bis(N,N'-dibenzylthiocarbamoyldithio)butane, 1,5-bis(N,N'-dibenzylthiocarbamoyldithio)pentane, 1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane, 1,7-bis(N,N'-dibenzylthiocarbamoyldithio)heptane, 1,8-bis(N,N'-dibenzylthiocarbamoyldithio)octane, 1,9-bis(N,N'-dibenzylthiocarbamoyldithio)nonane, and 1,10-bis(N,N'-dibenzylthiocarbamoyldithio)decane. Among these, 1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane is preferred because it is thermally stable and has excellent polarizability.

[0079] The content of the crosslinking agent capable of forming bonds including SC bonds between the polymers is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 8.0 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 4.0 parts by mass or less. By setting the content within the above range, good abrasion resistance tends to be obtained. In addition, the same range is also suitable when using a compound represented by formula (I) as the crosslinking agent. In addition, the lower limit or upper limit of the content of the crosslinking agent, the compound represented by formula (I), may be 2.0 parts by mass or 3.0 parts by mass.

[0080] Examples of the crosslinking agent capable of directly forming a C—C bond between polymers include organic peroxides, etc. The organic peroxide is not particularly limited, and any conventionally known compound can be used.

[0081] Examples of organic peroxides include acyl peroxides such as benzoyl peroxide, dibenzoyl peroxide, and p-chlorobenzoyl peroxide, peroxyesters such as 1-butyl peroxyacetate, t-butyl peroxybenzoate, and t-butyl peroxyphthalate, ketone peroxides such as methyl ethyl ketone peroxide, alkyl peroxides such as di-t-butyl peroxybenzoate and 1,3-bis(1-butylperoxyisopropyl)benzene, hydroperoxides such as t-butyl hydroperoxide, dicumyl peroxide, and t-butylcumyl peroxide. Among these, dicumyl peroxide and t-butylcumyl peroxide are preferred from the viewpoint of wear resistance.

[0082] The content of the crosslinking agent capable of directly forming a C-C bond between polymers is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 1.0 parts by mass or less, more preferably 0.8 parts by mass or less, and even more preferably 0.6 parts by mass or less. By setting the content within the above range, good abrasion resistance tends to be obtained. In addition, the same range is also suitable when an organic peroxide is used as the crosslinking agent. The lower limit or upper limit of the content of the crosslinking agent or organic peroxide may be 0.4 parts by mass.

[0083] As the zinc dithiophosphate, for example, a compound represented by the following general formula can be suitably used. Zinc dithiophosphate has a zinc atom at the center of its structure, and exhibits a superior crosslinking promoting effect compared to zinc oxide. By using zinc dithiophosphate, sufficient crosslinking can be achieved.

[0084] [ka] (In the formula, R 1 ~R 4 each independently represents a linear or branched alkyl group having 1 to 18 carbon atoms, or a cycloalkyl group having 5 to 12 carbon atoms.

[0085] R 1 ~R 4 Examples of the linear or branched alkyl group represented by R include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a 4-methylpentyl group, a 2-ethylhexyl group, an octyl group, and an octadecyl group, while examples of the cycloalkyl group include a cyclopentyl group, a cyclohexyl group, and a cyclooctyl group. Among these, R 1 ~R 4 is preferably a linear or branched alkyl group having 2 to 8 carbon atoms, more preferably an n-butyl group, an n-propyl group, an iso-propyl group, or an n-octyl group, and further preferably an n-butyl group.

[0086] Examples of zinc dithiophosphate include TP-50, ZBOP-S, and ZBOP-50 manufactured by Rhein Chemie, and compounds similar thereto (e.g., in the above formula, R 1 ~R 4 The alkyl group may be an n-butyl group, an n-propyl group, an isopropyl group or an n-octyl group.

[0087] The content of the zinc dithiophosphate (content of the active ingredient) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1.0 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 10.0 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 4.0 parts by mass or less. By setting the content within the above range, good wear resistance tends to be obtained. In addition, the same range is also suitable when using a compound represented by the general formula (zinc dithiophosphate) as zinc dithiophosphate. In addition, the lower limit or upper limit of the content of the zinc dithiophosphate or the compound represented by the general formula may be 0.75 parts by mass or 1.5 parts by mass.

[0088] The rubber composition may contain a vulcanization accelerator. In particular, when a crosslinking agent capable of forming a bond including an SC bond between sulfur and a polymer is used as a crosslinking agent, the use of the vulcanization accelerator can provide good vulcanization characteristics and excellent wear resistance.

[0089] Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide (DM(2,2'-dibenzothiazolyl disulfide)), and N-cyclohexyl-2-benzothiazylsulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); Examples of the vulcanization accelerators include sulfenamide-based vulcanization accelerators such as hexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazolyl sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenyl guanidine, di-orthotolyl guanidine, and orthotolyl biguanidine. These may be used alone or in combination of two or more. Among them, sulfenamide-based and thiazole-based vulcanization accelerators are preferred.

[0090] The content of the vulcanization accelerator is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 3.0 parts by mass or less, more preferably 2.0 parts by mass or less, and even more preferably 1.5 parts by mass or less. When the content is within the above range, good abrasion resistance tends to be obtained.

[0091] The rubber composition may contain a wax. The wax is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax; natural waxes such as vegetable wax and animal wax; and synthetic waxes such as polymers of ethylene, propylene, etc. Commercially available products include those from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Seiko Chemical Co., Ltd., etc. These may be used alone or in combination of two or more kinds. Among them, petroleum waxes are preferred, and paraffin wax is more preferred.

[0092] The amount of the wax per 100 parts by mass of the rubber component is preferably 0.5 part by mass or more, more preferably 1 part by mass or more, and preferably 10 parts by mass or less, more preferably 6 parts by mass or less.

[0093] The rubber composition preferably contains an antioxidant. The antioxidant is not particularly limited, and examples thereof include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylene Examples of the antioxidant include p-phenylenediamine antioxidants such as diamines; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. Commercially available products include those from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., and Flexis Co., Ltd. These may be used alone or in combination of two or more. Among them, p-phenylenediamine antioxidants (more preferably, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) are preferred.

[0094] The amount of the antioxidant is preferably 1.0 part by mass or more, more preferably 2.0 parts by mass or more, and is preferably 7.0 parts by mass or less, more preferably 6.0 parts by mass or less, based on 100 parts by mass of the rubber component.

[0095] The rubber composition preferably contains a fatty acid, in particular stearic acid. As the stearic acid, any known stearic acid can be used, for example, products available from NOF Corporation, NOF Corporation, Kao Corporation, Fujifilm Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., and the like.

[0096] The amount of the fatty acid is preferably 0.5 part by mass or more, and more preferably 1.0 part by mass or more, based on 100 parts by mass of the rubber component. Also, the amount is preferably 10.0 parts by mass or less.

[0097] The rubber composition preferably contains a zinc fatty acid. As the zinc fatty acid, a saturated zinc fatty acid having a plurality of carbon numbers, ie, 14 to 20, can be suitably used.

[0098] The content of fatty acid zinc is preferably 1.0 part by mass or more, more preferably 2.0 parts by mass or more, based on 100 parts by mass of the rubber component. The content is preferably 6.0 parts by mass or less, more preferably 4.0 parts by mass or less. If the total content exceeds 6.0 parts by mass, the abrasion resistance and elongation at break may decrease. Within the above range, good abrasion resistance tends to be obtained.

[0099] The rubber composition preferably contains zinc oxide. As the zinc oxide, any known zinc oxide can be used, for example, products available from Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., and the like.

[0100] The amount of zinc oxide is preferably 0.5 part by mass or more, more preferably 1.0 part by mass or more, based on 100 parts by mass of the rubber component, and is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less.

[0101] In addition to the above-mentioned components, the rubber composition may contain additives generally used in the tire industry, such as processing aids and surfactants.

[0102] A known method can be used to produce the rubber composition for treads (rubber composition for treads after vulcanization). For example, the rubber composition can be produced by kneading the above-mentioned components using a rubber kneading device such as an open roll, a Banbury mixer, or a kneader, and then vulcanizing the components.

[0103] As for the kneading conditions, in the base kneading process in which additives other than the crosslinking agent (vulcanizing agent) and the vulcanization accelerator are kneaded, the kneading temperature is usually 100 to 180°C, preferably 120 to 170°C. In the finish kneading process in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 120°C or less, preferably 85 to 110°C. In addition, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. The vulcanization temperature is usually 140 to 190°C, preferably 150 to 185°C. In addition, when an organic peroxide is used, secondary vulcanization may be performed as necessary. This removes unnecessary organic peroxides that could not be involved in the crosslinking and their residues, and can reduce the changes in Hs and Swell before and after heat aging.

[0104] The pneumatic tire of the present invention is manufactured by a conventional method using the above rubber composition. That is, the rubber composition containing the above components is extruded in an unvulcanized state to match the shape of a tread (a component that comes into contact with the road surface, such as a single-layer tread or a cap tread of a multi-layer tread) and other components, and molded in a conventional method on a tire building machine together with other tire components to form an unvulcanized tire. The unvulcanized tire is heated and pressurized in a vulcanizer to obtain a tire.

[0105] The tires can be used as passenger car tires, large passenger car tires, large SUV tires, heavy load tires such as trucks and buses, light truck tires, motorcycle tires, racing tires (high performance tires), and the like. EXAMPLES

[0106] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.

[0107] Various chemicals used in the examples and comparative examples will be collectively described below. NR:TSR20 SBR: JSR1502 (styrene content 23.5% by mass) manufactured by JSR Corporation BR: BR150B (cis content 98% by mass) manufactured by Ube Industries, Ltd. Fine particle carbon black: Carbon black for prototypes (N2SA181m 2 / g) Silica: Degussa ULTRASIL VN3 (N2SA175m 2 / g) Silane coupling agent: Si266 (bis(3-triethoxysilylpropyl) disulfide) manufactured by Evonik Degussa Oil: Diana Process NH-70S (aromatic process oil) manufactured by Idemitsu Kosan Co., Ltd. Wax: Ozoace 0355 manufactured by Nippon Seiro Co., Ltd. Antioxidant 6C: Nocrac 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Anti-aging agent FR: Antigen FR manufactured by Sumitomo Chemical Co., Ltd. (a quinoline-based anti-aging agent, made by refining the reaction product of amines and ketones, with no residual amines) Organic resin: Struktol 40MS (ethylene propylene styrene copolymer, softening point 78°C, EP content 82% by mass) manufactured by Struktol Zinc fatty acid: EF44 from Struktol Stearic acid: Tsubaki made by NOF Corporation Zinc oxide: Zinc oxide manufactured by Mitsui Mining & Smelting Co., Ltd. Sulfur: HK-200-5 (5% oil sulfur) manufactured by Hosoi Chemical Co., Ltd. Crosslinker 1: Vulcuren VP KA9188 (1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane) manufactured by LANXESS Crosslinker 2: Dicumyl peroxide Crosslinking agent 3: TP-50 manufactured by Rhein Chemie (a mixture of zinc dithiophosphate and polymer, R 1 ~R 4 n-Butyl group, active ingredient 50% by weight Vulcanization accelerator NS: Sancerer NS-G manufactured by Sanshin Chemical Industry Co., Ltd.

[0108] Examples and Comparative Examples According to the compounding recipes shown in Tables 1 to 4, chemicals other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 80°C using an open roll to obtain an unvulcanized rubber composition. The unvulcanized rubber composition obtained was press-vulcanized at 170°C for 20 minutes to obtain a vulcanized rubber composition.

[0109] The resulting unvulcanized rubber composition was molded into a tread shape, and laminated together with other tire components to prepare an unvulcanized tire. The tire was press-vulcanized at 170° C. for 10 minutes to obtain a test tire (size: 195 / 65R15). In addition, for Examples 1-4, 2-4, 3-4, and 4-4, after press vulcanization, both the vulcanized rubber composition and the test tire were subjected to secondary vulcanization at 120° C. for 2 hours using an oven or the like.

[0110] <Heat aging test> A new vulcanized rubber composition (before heat aging) was subjected to heat aging (100°C, 96 hours) in accordance with JIS K6257:2010 to obtain a vulcanized rubber composition after heat aging.

[0111] The obtained test tires, new tires, and vulcanized rubber compositions after heat aging (rubber compositions after vulcanization) were evaluated as follows. The results are shown in Tables 1 to 4. The reference comparative examples in Tables 1, 2, 3, and 4 are Comparative Examples 1-1, 2-1, 3-1, and 4-1, respectively.

[0112] (Rubber hardness (Hs)) For each test piece made of each vulcanized rubber sheet (vulcanized rubber composition) before and after heat aging, the Hs (hardness) of the new test piece and the test piece after heat aging were measured using a type A durometer in accordance with JIS K6253 "Testing method for hardness of vulcanized rubber and thermoplastic rubber" (measurement temperature 23°C ± 2°C).

[0113] (Degree of cross-linking (Swell)) Test pieces (20 mm x 20 mm x 2 mm) of each vulcanized rubber sheet (vulcanized rubber composition) before and after heat aging were immersed in toluene at 25°C for 24 hours, and the volume change (swell (%)) before and after immersion was measured.

[0114] (Wear resistance) Each test tire was fitted to a domestically produced FF vehicle, and the tire tread groove depth after 8,000 km of driving was measured. The driving distance when the tire groove depth was reduced by 1 mm was calculated and expressed as an index (wear resistance index) with the reference comparative example taken as 100. The higher the index, the longer the driving distance when the tire groove depth is reduced by 1 mm, indicating better wear resistance.

[0115] [Table 1]

[0116] [Table 2]

[0117] [Table 3]

[0118] [Table 4]

[0119] As can be seen from Tables 1 to 4, in the examples where the blending ratio was 10 mass % or more of SBR and 10 mass % or more of BR and the formulae (1) and (2) were satisfied, excellent abrasion resistance was obtained.

Claims

1. The content of styrene-butadiene rubber in 100% by mass of the rubber component is 10% by mass or more, and the content of butadiene rubber is 10% by mass or more, The content of silica per 100 parts by mass of the rubber component is 15 parts by mass or more, Contains isoprene rubber, and A rubber composition for treads, in which the absolute value of hardness change |ΔHs| before and after heat aging, measured using the following rubber hardness (Hs) and crosslinking degree (Swell) measurements before and after heat aging, satisfies the following formula (1), and the absolute value of Swell change |ΔSwell| before and after heat aging, satisfies the following formula (2). |ΔHs|≦2.5 (1) |ΔSwell|≦19% (2) <Heat aging test> The vulcanized rubber composition before heat aging is subjected to heat aging (100°C, 96 hours) in accordance with JIS K6257:2010 to obtain a vulcanized rubber composition after heat aging. (Measurement of Rubber Hardness (Hs)) For each test piece made of the vulcanized rubber composition before and after heat aging, Hs (hardness) of the test piece before and after heat aging is measured using a type A durometer in accordance with JIS K6253 "Testing method for hardness of vulcanized rubber and thermoplastic rubber" (measurement temperature 23°C ± 2°C). (Measurement of Cross-Linking Degree (Swell)) Each test piece (20 mm x 20 mm x 2 mm) of the vulcanized rubber composition before and after heat aging is immersed in toluene at 25°C for 24 hours, and the volume change (Swell (%)) before and after immersion is measured.

2. The content of styrene butadiene rubber in 100% by mass of the rubber component is 10% by mass or more, and the content of butadiene rubber is 10% by mass or more, The content of silica per 100 parts by mass of the rubber component is 15 parts by mass or more, Contains only non-sulfur crosslinkers, and A rubber composition for treads, in which the absolute value of hardness change |ΔHs| before and after heat aging, measured using the following rubber hardness (Hs) and crosslinking degree (Swell) measurements before and after heat aging, satisfies the following formula (1), and the absolute value of Swell change |ΔSwell| before and after heat aging, satisfies the following formula (2). |ΔHs|≦2.5 (1) |ΔSwell|≦19% (2) <Heat aging test> The vulcanized rubber composition before heat aging is subjected to heat aging (100°C, 96 hours) in accordance with JIS K6257:2010 to obtain a vulcanized rubber composition after heat aging. (Measurement of Rubber Hardness (Hs)) For each test piece made of the vulcanized rubber composition before and after heat aging, Hs (hardness) of the test piece before and after heat aging is measured using a type A durometer in accordance with JIS K6253 "Testing method for hardness of vulcanized rubber and thermoplastic rubber" (measurement temperature 23°C ± 2°C). (Measurement of Cross-Linking Degree (Swell)) Each test piece (20 mm x 20 mm x 2 mm) of the vulcanized rubber composition before and after heat aging is immersed in toluene at 25°C for 24 hours, and the volume change (Swell (%)) before and after immersion is measured.

3. The content of styrene butadiene rubber in 100% by mass of the rubber component is 10% by mass or more, the content of butadiene rubber is 10% by mass or more, and the content of isoprene-based rubber is 25% by mass or more, The content of silica per 100 parts by mass of the rubber component is 15 parts by mass or more, and A rubber composition for treads, in which the absolute value of hardness change |ΔHs| before and after heat aging, measured using the following rubber hardness (Hs) and crosslinking degree (Swell) measurements before and after heat aging, satisfies the following formula (1), and the absolute value of Swell change |ΔSwell| before and after heat aging, satisfies the following formula (2). |ΔHs|≦2.5 (1) |ΔSwell|≦19% (2) <Heat aging test> The vulcanized rubber composition before heat aging is subjected to heat aging (100°C, 96 hours) in accordance with JIS K6257:2010 to obtain a vulcanized rubber composition after heat aging. (Measurement of Rubber Hardness (Hs)) For each test piece made of the vulcanized rubber composition before and after heat aging, Hs (hardness) of the test piece before and after heat aging is measured using a type A durometer in accordance with JIS K6253 "Testing method for hardness of vulcanized rubber and thermoplastic rubber" (measurement temperature 23°C ± 2°C). (Measurement of Cross-Linking Degree (Swell)) Each test piece (20 mm x 20 mm x 2 mm) of the vulcanized rubber composition before and after heat aging is immersed in toluene at 25°C for 24 hours, and the volume change (Swell (%)) before and after immersion is measured.

4. The rubber composition for a tread according to any one of claims 1 to 3, wherein |ΔHs| and |ΔSwell| satisfy the following formulas. |ΔHs|≦2.0 |ΔSwell|≦15%

5. The rubber composition for a tread according to any one of claims 1 to 3, wherein |ΔHs| and |ΔSwell| satisfy the following formulas. |ΔHs|≦1.5 |ΔSwell|≦10%

6. The rubber composition for a tread according to any one of claims 1 to 3, wherein |ΔHs| and |ΔSwell| satisfy the following formulas. |ΔHs|≦1.0 |ΔSwell|≦5%

7. The rubber composition for a tread according to any one of claims 1 to 3, wherein |ΔHs| and |ΔSwell| satisfy the following formulas. |ΔHs|≦0.5 |ΔSwell|≦4%

8. The rubber composition for treads according to claim 1 or 3, which contains sulfur and a crosslinking agent other than sulfur.

9. The rubber composition for treads according to any one of claims 1 to 7, which contains only a crosslinking agent other than sulfur.

10. The rubber composition for treads according to any one of claims 1 to 9, wherein the content of the isoprene-based rubber in 100% by mass of the rubber component is 25% by mass or more.

11. A pneumatic tire having a tread made of the rubber composition according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Rubber composition for tire, and pneumatic tire

    JP2011132305A

  • Rubber composition for cap tread and studless tire

    JP2012219124A

  • Rubber composition for tread, and pneumatic tire

    JP2013001805A

  • Pneumatic tire with thread

    US20120083559A1

  • Rubber composition and pneumatic tire

    WO2018105230A1